post-traumatic stress disorder among amputeesAs a result of the Syrian crisis In a light of some variables. “ A field study in Zahi Azrak hospital in Lattakia city” - Sadi , Reema; Shrebah , Bushra; Shaleesh , Asema (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The purpose of current research is to identify the level of post-traumaticstress disorder among amputees in Zahi Azrak hospital in Lattakia city, and Identify the differences in this disorder according to some variables (the social situation, educational level, place of amputation), The study sample consisted of (40) amputee in Zahi Azrak hospital, it has been using the post-traumatic disorderscale for Davidson, Arabization by Dr. Abd Alazez, The results indicated that percentage (14%) of respondents suffer from symptoms of the disorder is highly, and (42.5%) moderately, and (42.5%) did not appear to have symptoms of the disorder, the results also indicated that there were no statistically significant differences between Among respondents on post-traumaticstress disorder scale according to variables Search (the social situation, educational level, place of amputation)